On Integral Transforms and Matrix Functions - Hassan Eltayeb; Adem Kılıçman; Ravi P. Agarwal (Abstract and Applied Analysis)
The Sumudu transform of certain elementary matrix functions is obtained. These transforms are then used to solve the differential equation of a general linear conservative vibration system, a vibrating system with a special type of viscous damping.